A concise review on influenza - Ayanar, Pratibha L.; Jamadar, Simran M.; Bharati, Shweta R.; Ghanwat, Aishwarya R.; Pawar, Kumudini R. (International Journal of Research in Medical Sciences, 2025)
Influenza, commonly known as the flu, is a contagious respiratory illness caused by influenza viruses. It can lead to mild to severe illness and can result in hospitalization and death. The flu virus is characterized by its ability to mutate, leading to seasonal epidemics and occasional pandemics. Understanding the types, risk factors, history, symptoms, causes, treatment, and mechanisms of action is crucial for effective prevention and management. It is classified into four types: A, B, C, and D, with types A and B being responsible for the seasonal flu epidemics. The flu is highly contagious and spreads through respiratory droplets when an infected person coughs, sneezes, or talks. The history of influenza dates back centuries, with notable pandemics occurring in 1918 (Spanish flu), 1957 (Asian flu), 1968 (Hong Kong flu), and the H1N1 pandemic in 2009. The 1918 pandemic was particularly devastating, infecting about one-third of the world's population and resulting in millions of deaths. For treatment of flu, vaccination is most effective method. This review focused on the symptoms, causes, treatment and mechanism of action of antiviral drug.